Moyamoya disease: report of three cases in Brazilian patients - CLÉLIA MARIA RIBEIRO FRANCO; MARCIA MAIUMI FUKUJIMA; ROBERTO DE MAGALHÃES CARNEIRO DE OLIVEIRA; ALBERTO ALAIN GABBAI (Arquivos de Neuro-Psiquiatria)
Moyamoya disease (MMD) is a chronic occlusive cerebrovascular disease of unknown etiology reported mainly in the Japanese. Most cases occur in children. The disease is rare in non-Oriental adults manifesting itself mostly as intracerebral hemorrhages. We describe MMD in 2 non-Oriental young adults and one adolescent that developed cerebral infarctions. The adults were medicated with aspirin and no medication was given to the adolescent. All patients did not deteriorate in a follow-up period from 1 to 4 years. Although rare, MMD is an important cause of stroke in young individuals and may well be underreported: only 18 patients have been reported till 1997 in Brazil. Neurologists should include MMD in differential diagnosis of ischemic and hemorrhagic strokes in young adults.